2008
DOI: 10.1254/jphs.fp0071606
|View full text |Cite
|
Sign up to set email alerts
|

Vulnerability of Gastric Mucosa to Prednisolone in Rats Chronically Exposed to Cigarette Smoke

Abstract: Abstract. We examined gastric mucosal vulnerability in a rat model of chronic obstructive pulmonary disease (COPD). Male Wistar rats were exposed to cigarette smoke for 12 weeks (CSE rats), and on the last 4 days of exposure, prednisolone was given to induce gastric mucosal injury. Histopathology, pulmonary function, arterial blood gases, and levels of lipid peroxides (LPO), prostaglandin E 2 (PGE 2 ), hypoxia-inducible factor 1 alpha subunit (HIF-1α), and vascular endothelial growth factor (VEGF) in gastric m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…They found the increased HIF-1α and VEGF expression in NSCLC cells after the treatment of nicotine [22]. Takeuchi et al reported that the levels of HIF-1α had been increased after the male Wistar rats were exposed to cigarette smoke for 12 weeks (CSE rats) [23]. Moon HE revealed that MTA1 has deacetylation activity on HIF-1α in vivo by immunoprecipitation and acetylation assays, and MTA1 increased the transcriptional activity of HIF-1α by stabilization of the HIF-1α protein [24].…”
Section: Discussionmentioning
confidence: 99%
“…They found the increased HIF-1α and VEGF expression in NSCLC cells after the treatment of nicotine [22]. Takeuchi et al reported that the levels of HIF-1α had been increased after the male Wistar rats were exposed to cigarette smoke for 12 weeks (CSE rats) [23]. Moon HE revealed that MTA1 has deacetylation activity on HIF-1α in vivo by immunoprecipitation and acetylation assays, and MTA1 increased the transcriptional activity of HIF-1α by stabilization of the HIF-1α protein [24].…”
Section: Discussionmentioning
confidence: 99%
“…Cigarette smoke (CS) is considered to be the primary risk factor for the development of pulmonary emphysema (4). CS contains greater than 1014 free radicals, including reactive oxygen and reactive nitrogen species per puff, which impose a strong oxidative burden resulting in an oxidant/antioxidant imbalance (5).…”
Section: Introductionmentioning
confidence: 99%
“…The doses of rolipram and dexamethasone were used in the present study based on our preliminary results and previous studies [14,15]. CS and LPS treatment was performed as follows: rats were confined in a container made of plexiglass (85 cm× 85 cm× 45 cm), and pump CS from 12 standard cigarettes into the container, and rats were exposed to the smoking for 20 min, twice a day with an interval of 15 min and 6 days per week, LPS was administrated intratracheally every 4 weeks at a dose of 1 mg/kg, it took 12 weeks to establish a rat COPD-like animal model [16][17][18][19]. Zl-n-91, rolipram and dexamethasone were diluted in 60% Polyethylene glycol and administrated intraperitoneally for 8 weeks from the fifth week.…”
Section: Methodsmentioning
confidence: 99%